The Colonialists & Indigenous Exchange Currency: Tracing the Genesis of Socioeconomic Woes in Postcolonial Nigeria - Samuel O, Okafor (International Journal of Sustainable Development & World Policy, 2019)
The problem of colonialism continues to emerge in all aspects of the lives of the colonized and even raise some unseen complications following, the trajectory of the covertly structured system by the colonial agents. Among the African nations colonized, their economy, political system and the host of other institutions are still in the trajectory of the colonially structured concepts and precepts. In Nigeria in particular, almost every facet of Nigerian life as a nation still suffer the injuries of colonialism covertly buried at the root of all public institutions. Although the problem of colonialism and the impacts are many in different aspects of the Nigerian national life, this study was focused on the undermining of the African traditional exchange system in what later became Nigeria and how such manipulation offset the present currency abuse among Nigerians and the problem of underdevelopment. The study utilized the available Historical, Anthropological and Archaeological information to explain the present economic and general system disorder in Nigeria. Nonetheless, the paper established knowledge-based policy strategies towards downgrading unfavourable bilateral relationship sustaining the vestiges of colonial venoms, which have subverted developmental efforts in Nigeria and other colonized nations.